High-content fluorescence bioassay investigates pore formation, ion channel modulation and cell membrane lysis induced by venoms - Simon Kramer; Charan Kotapati; Yuanzhao Cao; Bryan G. Fry; Nathan J. Palpant; Glenn F. King; Fernanda C. Cardoso (Toxicon: X, 2024)
Venoms comprise highly sophisticated bioactive molecules modulating ion channels, receptors, coagulation factors, and the cellular membranes. This array of targets and bioactivities requires advanced high-content bioassays to facilitate the development of novel envenomation treatments and biotechnological and pharmacological agents. In response to the existing gap in venom research, we developed a cutting-edge fluorescence-based high-throughput and high-content cellular assay. This assay enables the simultaneous identification of prevalent cellular activities induced by venoms such as membrane lysis, pore formation, and ion channel modulation. By integrating intracellular calcium with extracellular nucleic acid measurements, we have successfully distinguished these venom mechanisms within a single cellular assay. Our high-content bioassay was applied across three cell types exposed to venom components representing lytic, ion pore-forming or ion channel modulator toxins. Beyond unveiling distinct profiles for these action mechanisms, we found that the pore-forming latrotoxin α-Lt1a prefers human neuroblastoma to kidney cells and cardiomyocytes, while the lytic bee peptide melittin is not selective. Furthermore, evaluation of snake venoms showed that Elapid species induced rapid membrane lysis, while Viper species showed variable to no activity on neuroblastoma cells. These findings underscore the ability of our high-content bioassay to discriminate between clades and interspecific traits, aligning with clinical observations at venom level, beyond discriminating among ion pore-forming, membrane lysis and ion channel modulation. We hope our research will expedite the comprehension of venom biology and the diversity of toxins that elicit cytotoxic, cardiotoxic and neurotoxic effects, and assist in identifying venom components that hold the potential to benefit humankind.